PENERAPAN METODE ROLE PLAYING DALAM MENINGKATKAN KETERAMPILAN BERBICARA SISWA PADA PEMBELAJARAN BAHASA INDONESIA DI KELAS IV SD NEGERI OETONA KOTA KUPANG - Sofia Godeliva Un Lala; Alswareni Nomnafa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Formulation of the problem of how the application of the role playing learning method can improve the Indonesian speaking sklills of class IV students at SDN Oetona Kupang. The aim is to improve Indonesian speaking sklills through the application of the role playing learning method in class IV of SDN Oetona Kupang. The method used is Classroom Action Reseatch through two cycles, each cycle consisting of four stages, namely planning, implementation, observation and reflection. Data collection techniques are observation techniques, tests and documentation studies. The data analysis technique uses qualitative and quantitative descriptive. The research was carried out at SDN Oetona Kupang, the results of research on students’ speaking skills in cyle I were in the category of not yet achieving completeness, remidial in the requirt parts with an average score of 53,72% and individually of the 27 students only 12 students 44,44%, completed or achieving the Criteria for Completion of Learning Objectives. Meanwhille, students’ speaking skills in cycle II were in the category of having achieved completeness, no need for remidial work with an average score of 75,92% and individually 27 students had achieved the Criteria for Complete Learning Objective. Students’ speaking skills have increased, this can be seen from cycle I and cycle II, namely from 53,72% to 75,92%. Based on the results of the research above, it can be concluded that there has been an incrase in students’ speaking skills in learning using the role playing method in class IV of SD Negeri Oetona Kupang.